Edilgen Çatılı Cümlelerin Nesirdeki Yeri / The Role of Passive Voice Structure in Turkish Prose Literature - Avcı, Yusuf; Çiçek, Sema (Journal of History Culture and Art Research, 2018)
Abstract This research aims to display to what extent the usage of the passive voice structure which we come accross frequently in recent in Turkish prose literature. In this research, the number of the sentences in the first fifty pages of different genres such as novels, stories or essays were examined and the rates of passive voice structure usage in these sentences were calculated. Additionally, the first ten pages of the dissertations were examined while the essays and columns in journals were examined totally within the scope of passive voice usage. The differences and the similarities in the usage of passive voice structure in the works written in different genres, in different times, about different subjects and by the writers who has different worldviews, are compared. The variables mentioned in previous sentence were also examined whether they have any effect on the usage of the passive voice. As a result of the survey, less usage of the passive voice was detected in the writings which centered around events and actions than in the thought-based writings. It was also observed and obtained from the data gathered from the examined works that there is not an obvious difference between the amount of the usage of passive voice of the writers who have different philosophy, lifestyle or world view. Consequently, it is concluded that the usage of passive voice is an individual choice. It is known that Turkish society value the person and is famous for its being active, however the scociety is possibly in danger of losing its characteristics by widening the usage of the passive sentence structures since the event is more important rather than the person in passive voice. Therefore it should be said that the usage of passive voice is not appropriate for the active structure of Turkish society. Moreover, this passieveness faciliates the work of provocators in motivating the society to the negative movements. Öz Bu araştırma son zamanlarda sık sık karşılaştığımız edilgen çatılı cümle kullanımının nesirde ne boyutta olduğunu tespit etmeyi amaçlamaktadır. Araştırmada roman, hikâye, deneme gibi farklı türlerde yazılmış eserlerin ilk elli sayfasındaki cümle sayıları incelenerek bu cümlelerdeki edilgen çatı kullanım oranları hesaplanmıştır. İncelenen tezlerin ilk on sayfasında edilgen çatı kullanım oranlarına, makale ve köşe yazılarının ise tamamındaki cümle sayısına göre edilgen çatı kullanım oranlarına bakılmıştır. Farklı türlerde, farklı zamanlarda, farklı konularda ve farklı görüşlere sahip yazarlar tarafından yazılmış eserlerde edilgen çatılı cümle kullanım oranlarındaki benzerlikler ve farklılıklar karşılaştırılmıştır. Bu çeşitli değişkenlerin edilgen çatılı cümle kullanımı üzerinde etkili olup olmadığı da tespit edilmeye çalışılmıştır. Elde edilen bulgular, olay çevresinde gelişen yazı türlerinde edilgen yapılı cümle kullanımının düşünce yazılarına oranla daha az kullanıldığını göstermiştir. Ayrıca, taranan eserlerde farklı dünya görüşüne sahip farklı yazarların edilgen çatılı kullanım oranlarında bariz bir değişiklik olmadığı görülmüştür. Edilgen cümle yapısında öznenin geri plana atılması nedeniyle bu tür bir kullanımın, aktif olma ve insanı öne çıkartma özelliğiyle bilinen Türk toplumu için uygun olmadığı öngörülmüştür. Ayrıca edilgen olma kültürünün yaygın olduğu bir toplumda ortaya çıkabilecek toplumsal hareketlerde provokatörlerin çok daha rahat bir şekilde yönlendirme yapabileceği tespiti yapılmıştır.